Green Property Research Trends: A Bibliometric Analysis - Kusuma, Melia; Isa, Muzakar; Sholahuddin, Muhammad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to map global research trends related to green property using a bibliometric approach.Methodology: Publication data were collected from scholarly databases and filtered by publication year, field of study, document type, publication stage, language, accessibility, and full access availability. The selected articles were analyzed using bibliometric tools, including VOSviewer and Bibliometrix-R.Results: The analysis shows a significant increase in publications on green property since 2018. Sustainability (Switzerland) appears as the primary publication source, while Chuweni, N.N. and Fauzi, N.S. are identified among productive authors. Main topics include green housing, energy efficiency, and environmentally friendly buildings.Applications/Originality/Value: This research contributes to the expansion of green property literature and provides recommendations for future studies focusing on energy efficiency policies, green certification, green infrastructure, and sustainable property development.